Neo-Arian Controversy: The Trinitarian Theology of Eunomius - Vladimir KНARLAMOV (Богословські роздуми: Східноєвропейський журнал богословʼя)
This article provides a concise assessment of the Trinitarian theology of Eunomius (d. 394). Eunomius was one of the most influential leaders of the neo-Arian group active in the second half of the fourth century. In Eunomius we find a very intricate and philosophically oriented system that attempted to offer a rational and coherent explanation of the Trinitarian doctrine. He was an eloquent and original thinker. A number of Christian Fathers, including Basil of Caesarea and Gregory of Nyssa, refuted his teaching. Generally, the theology and works of Eunomius are not known to the Russian reading audience, except for some references to him in now outdated publications of the late nineteenth and early twentieth century.